Dissemination of Geographical Indication Potential: An Effort to Protect Tourism Intellectual Property - Triyono Adi Saputro; Vadira Hanami; Teguh Hartono; Iwan Hertanto (Universitas Muhammadiyah Purwokerto, 2023)
The urgency of intellectual property protection is the main key in increasing competitiveness in global competition. Sragen Regency has great potential to obtain legal protection on intellectual property sourced from the industrial and tourism sectors. This qualitative and normative study used secondary data and a normative juridical approach. Based on the analysis with Law Number 20 of 2016 on Brands and Geographical Indications, Sragen Regency has products to be protected with geographical indications, namely the Sangiran Stone craft located at the Museum Manusia Purba Sangiran. This condition strengthens geographical indications in Sragen as intellectual property considering that the tourism sector has a very large correlation with the industrial sector. Dissemination can be carried out by the government and stakeholders as a form of encouragement and support for groups of business actors in the Sragen area so that they are aware of the law and understand the essence of law so that they can obtain legal protection for Sangiran stone crafts through geographical indications as intellectual property in Sragen Regency.Keywords: Geographical indications, Intellectual Property, Tourism